Violent Conflicts, Human Rights and the Fate of the African Child - Ojo, Olayinka Olabimpe (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Children are said to be the leaders of tomorrow, and the only way they can become good leaders of tomorrow is through education and the reinforcement of social values. Also, by inculcating societal norms and standards in them at an early age which will go a long way in moulding them to secure a good future for them in the society. This will in tum have the rippling effect of creating a descent society. This goal can however be achieved, only if a conducive environment is created to tender and nurture the greatness in them. The family and the community at large play an essential role in order to attain this objective of helping a child to lead a meaningful life. During wars the family structure and communal bond is attacked, everyman struggles for himself, and the survival instinct comes into play. However, children by their very nature are naive, harmless and extremely vulnerable, yet they are exploited and taken advantage of by those who are expected to take care of them. It is sad to note that in times of war, they are subjected to varying degrees of horror. Even though they are by no means the cause of the conflict; nevertheless, they are made to reap what they did not sow, children are subjected to most extreme cases of violence. This work advocates that great premium should be placed on the rights of a child, such that it would discourage violation. This paper further discusses some of the humiliating and horrifying experiences children go through in times of war.